Autism-related traits are related to effectiveness of immersive visual guidance on spatial cognitive ability: a pilot study - Harada, Yuki; Wada, Makoto (Frontiers in Virtual Reality, 2023)
A head-mounted display could potentially restrict users’ visual fields and thereby impair their spatial cognitive ability. Spatial cognition can be assisted with immersive visual guidance. However, whether this technique is useful for individuals with autism-spectrum disorder (ASD) remains unclear. Given the recent virtual reality (VR) contents targeting individuals with ASD, the relationship between ASD-related traits and the effectiveness of immersive visual guidance should be clarified. This pilot study evaluated how ASD-related traits (autistic traits and empathizing–systemizing cognitive styles) among typically developing individuals are related to the effectiveness of visual guidance. Participants performed visual search and spatial localization tasks while using immersive visual guidance. In the visual search task, participants searched immersive VR environments for a target object and pushed a button according to the target color as quickly as possible. In the localization task, they viewed immersive visual guidance for a short duration and localized the guided direction via a controller. Results showed that visual search times were hastened with systemizing cognition. However, ASD-related traits were not significantly related to localization accuracy. These findings suggest that immersive visual guidance is generally useful for individuals with higher ASD-related traits.